(untitled) (Bangladesh Journal of Botany, 2024)
In recent years, the improvement and utilization of saline-alkaline soil has gradually shifted from engineering measures to biological measures. As a salt-tolerant plant, the reed has been preliminarily proven to have a role in improving saline-alkaline land. In order to explore the long-term effect of planting unharvested reeds on the improvement of saline-alkaline land, a pilot plot was set up in Fuping Pilot Test Base (34° 42’180"E; 109°11’49" N) near Lubo Beach, Fuping, Shaanxi, in 2012 to ascertain the improvement effect of long-term reed cultivation on saline–alkaline land. The objective was to study the long-term changes in soil pH, electrical conductivity, Ca2+, Mg2+, Cl-, SO42-, HCO3-, and CO32- contents, soil particle size and soil fertility. Results showed that (i) reed cultivation could effectively reduce soil salinization in the long term. From 2012 to 2022, the average pH of saline soil decreased from 9.42 to 8.86, and the electrical conductivity decreased from 1.20 μS/cm to 0.70 μS/cm. (ii) Reed cultivation considerably reduced the contents of Ca2+, Mg2+, Cl-, SO42-, HCO3-, and CO32- in the soil in the long term, and the reduction in each index was 5.9, 41.7, 63.5, 90.6, 81.7, 90.6, 77.9and 90.3%, respectively. (iii) Reed cultivation changed the soil structure. The soil texture of the 0–60 cm soil layer changed from silty sandy loam to silty loam from 2018 to 2022. (iv) Long-term reed planting without harvesting effectively improved soil fertility. In 2012, the content of soil organic matter was only 2.74 g/kg, but in 2022, the value reached 12.8 g/kg. Reed planting improved the physical and chemical properties of saline soil. Therefore, biological restoration of reed can be considered in low-lying saline–alkaline areas with high water volumes. Bangladesh J. Bot. 53(3): 665-672, 2024 (September) Special